2018
DOI: 10.1021/acs.cgd.7b00125
|View full text |Cite
|
Sign up to set email alerts
|

Particle Breakage: Limiting Conditions for Crystal–Crystallizer Collisions

Abstract: Two prominent theories surround the origin of secondary nuclei in batch crystallization experiments. Traditionally, the generation of secondary nuclei has been attributed to attrition breeding, resulting from collisions between crystals, impeller, and vessel geometry. Mechanistically, it is assumed that the collision of crystals leads to the generation of fine particles and nucleation sites. More recently, an alternative mechanism has received considerable attention, namely, cluster breeding secondary nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…In large volume stirred batch crystallizers it is even more difficult to quantify the effect of secondary nucleation. Tyrrell et al have shown that the fluid dynamics of a moving impeller might protect crystals from attrition in a large volume crystallizer 164 . Protection from the impeller alone is, however, not enough to prevent secondary nuclei: experiments have shown that fluid flow (shear) is sufficient to generate secondary nuclei 165 , although it has also been reported that this shear nucleation might be less effective 166 .…”
Section: Secondary Nucleation?mentioning
confidence: 99%
“…In large volume stirred batch crystallizers it is even more difficult to quantify the effect of secondary nucleation. Tyrrell et al have shown that the fluid dynamics of a moving impeller might protect crystals from attrition in a large volume crystallizer 164 . Protection from the impeller alone is, however, not enough to prevent secondary nuclei: experiments have shown that fluid flow (shear) is sufficient to generate secondary nuclei 165 , although it has also been reported that this shear nucleation might be less effective 166 .…”
Section: Secondary Nucleation?mentioning
confidence: 99%
“…Traditionally, secondary nucleation has been largely attributed to microbreakages of seed crystals caused by crystal-impeller collisions, 3 that is, attrition. 1 , 4 , 5 However, recent research has noted that this mechanism cannot describe secondary nucleation completely, 3 , 6 13 based on two main reasons. First, secondary nucleation can occur even when the crystal microbreakages are prevented by precluding any crystal-impeller collision.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above mentioned results, a mechanism of calcined gibbsite breakage is proposed and given in Figure 4c and d. The gibbsite particle breakage on the crystallite is initiated by the cracks on the surface, since the cracks are reported to be fragile parts where the stress caused by external force is likely to accumulate 18,19 . The breakage then extends into the crystallite and causes the cleavage of crystallites.…”
Section: The Breakage Mechanism Of Calcined Gibbsite Particle Under Ementioning
confidence: 99%
“…The calcination ramping rate and the size of crystallites consisting of gibbsite particles can influence the calcined gibbsite particle strength by influencing the total crack volume and crack width distribution on the calcined particles since cracks can be the defect point where breakage is likely to be initiated 18,19 . The particle embrittlement caused by cracks is more significant in gibbsite particles consisting of larger crystallites and calcined with lower ramping rates since these samples tend to generate cracks with increased total volume and crack width distribution.…”
Section: The Impact Of Calcination Temperature Crystallite Size and mentioning
confidence: 99%
See 1 more Smart Citation